The marine crocodile Maledictosuchus (Thalattosuchia, Metriorhynchidae) from the Kimmeridgian deposits of Tlaxiaco, Oaxaca, southern Mexico. Issue 4 (4th July 2018) - Barrientos-Lara, Jair I.; Alvarado-Ortega, Jesús; Fernández, Marta S.
Abstract: Metriorhynchidae is a family of highly specialized, extinct marine crocodylomorphs that inhabited the Paleopacific Ocean and the Tethys Sea during the Jurassic and the Early Cretaceous. Numerous metriorhynchid fossil specimens have been recovered from European and South American localities, but North American records of this family are still scarce. Here, we describe a recently recovered Kimmeridgian metriorhynchid from the Sabinal Formation, Tlaxiaco Basin, Oaxaca, Mexico, that is attributable to the genus Maledictosuchus . This genus was known previously from a single species, M. riclaensis, from the Middle Jurassic of Spain. The characteristics of this Mexican specimen support its identification as a new species, Maledictosuchus nuyivijanan, sp. nov. The two species differ in dental and skull-roof morphology. The frontal of M. nuyivijanan, sp. nov., has a wide, rounded anterior end that extends rostrally to the same level of the anterior end of the prefrontal, whereas the frontal of M. riclaensis has a narrow anterior end that is located posterior to the anterior end of the prefrontal. Additionally, the teeth of M. nuyivijanan, sp. nov., exhibit bicarinated crowns, a smooth labial surface, and a lingual surface ornamented with longitudinal ridges, whereas those of M. riclaensis lack carinae and the labial and lingual surfaces are covered with considerably more conspicuous ridges. The North American occurrence of M. nuyivijanan, sp. nov., suggests a wider temporal and geographic distribution for the genus Maledictosuchus across the Tethys Sea than previously thought: from the Callovian in Europe to the Kimmeridgian in southern North America. http://zoobank.org/urn:lsid:zoobank.org:pub:6F6CC892-B6E1-4069-AF3A-D05792AC0F7A SUPPLEMENTAL DATA—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Barrientos-Lara, J. I., J. Alvarado-Ortega, and M. S. Fernández. 2018. The marine crocodile Maledictosuchus (Thalattosuchia, Metriorhynchidae) from the Kimmeridgian deposits of Tlaxiaco, Oaxaca, southern Mexico. Journal of Vertebrate Paleontology. DOI:10.1080/02724634.2018.1478419.